A Radiological Study of the Morphological Variations in the Odontoid Process of the Axis Vertebra, Benghazi - Makhlouf , Fatma Awad; Alzentani , Seraj; Mohammed , Fatima Alhadi (Scientific Journal of University of Benghazi, 2023)
Background: The axis vertebra (C2) is atypical in its shape and morphological characteristics and forms an integral part of the craniovertebral junction. Aims: to measure height, AP and transverse diameters of the odontoid process of Libyan subjects using CT scans and to compare the results of the present study with the results of other studies conducted by different authors in different populations. Method: A descriptive, retrospective study was used by reviewing 167 CT scan images that were randomly selected from the CT suit of the Radiology Department at Aljalaa Hospital for Surgery and Accidents in Benghazi from April to July 2019. Patients with gross pathology or degenerative bone disease and those with evidence of an injury to the upper cervical spine were excluded from the study. The measurements of the odontoid process (height, AP and transverse diameters) were assessed. The data was entered and analyzed by using SPSS version 22. Results: The mean and median of the dens height of the odontoid process were nearly equal, with minimal & maximum values of 12.70 &17.60 mm respectively. Regarding the anteroposterior diameter of the process, the mean & median were nearly equal (11.18 & 11.30 mm respectively). The minimum & maximum values were (9.10 & 13.10 mm respectively). The mean ± SD of the transverse diameter was 9.04 ± 0.63 mm. Conclusion: The knowledge of these dimensions can provide useful information for the safe planning of osseous fixation and understanding of the development of the odontoid process, both in normal and in variant forms. Additionally, its phenotypical morphology is a prerequisite for the diagnosis and treatment of patients presenting with disorders affecting the craniocervical spine.